Comparison of Stemness and Gene Expression between Gingiva and Dental Follicles in Children - Chung-Min Kang; Seong-Oh Kim; Mijeong Jeon; Hyung-Jun Choi; Han-Sung Jung; Jae-Ho Lee (Stem Cells International)
The aim of this study was to compare the differential gene expression and stemness in the human gingiva and dental follicles (DFs) according to their biological characteristics. Gingiva (n=9) and DFs (n=9) were collected from 18 children. Comparative gene expression profiles were collected using cDNA microarray. The expression of development, chemotaxis, mesenchymal stem cells (MSCs), and induced pluripotent stem cells (iPSs) related genes was assessed by quantitative reverse transcription-polymerase chain reaction (qRT-PCR). Histological analysis was performed using hematoxylin-eosin and immunohistochemical staining. Gingiva had greater expression of genes related to keratinization, ectodermal development, and chemotaxis whereas DFs exhibited higher expression levels of genes related to tooth and embryo development. qRT-PCR analysis showed that the expression levels of iPSc factors including SOX2, KLF4, and C-MYC were 58.5±26.3, 12.4±3.5, and 12.2±1.9 times higher in gingiva and VCAM1 (CD146) and ALCAM (CD166) were 33.5±6.9 and 4.3±0.8 times higher in DFs. Genes related to MSCs markers including CD13, CD34, CD73, CD90, and CD105 were expressed at higher levels in DFs. The results of qRT-PCR and IHC staining supported the microarray analysis results. Interestingly, this study demonstrated transcription factors of iPS cells were expressed at higher levels in the gingiva. Given the minimal surgical discomfort and simple accessibility, gingiva is a good candidate stem cell source in regenerative dentistry.